19th AIAA Applied Aerodynamics Conference 2001
DOI: 10.2514/6.2001-2407
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of a wing with multiple winglets

Abstract: This effort examined the potential of multi-winglets for the reduction of induced drag without increasing the span of aircraft wings. Wind tunnel models were constructed using a NACA 0012 airfoil section for the untwisted, rectangular wing and flat plates for the winglets. Testing of the configurations occurred over a range of Reynolds numbers from 161,000 to 300,000. Wind tunnel balances provided lift and drag measurements, and laser flow visualization obtained wingtip vortex information.The Cobalt 60 unstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 7 publications
2
23
0
Order By: Relevance
“…Another study by Bagwill et al (1994) using VLM (vortex lattice method) model investigated winglets for RPV'S (Remotely piloted vehicles) and concluded that winglets increase efficiency for all cases, though the comparison was made only on the wing without winglet for inviscid cases. Smith et al (2001) have investigated multiple winglets mimicking the wingtip feathers during soaring and found them to help in the diffusion of the wingtip vortices. However such optimization is based mainly on reducing drag due to lift and increasing L/D with little regard to the physical structures that would be necessary to support such a design.…”
Section: Induced Drag and Conventional Wing Tip Researchmentioning
confidence: 99%
“…Another study by Bagwill et al (1994) using VLM (vortex lattice method) model investigated winglets for RPV'S (Remotely piloted vehicles) and concluded that winglets increase efficiency for all cases, though the comparison was made only on the wing without winglet for inviscid cases. Smith et al (2001) have investigated multiple winglets mimicking the wingtip feathers during soaring and found them to help in the diffusion of the wingtip vortices. However such optimization is based mainly on reducing drag due to lift and increasing L/D with little regard to the physical structures that would be necessary to support such a design.…”
Section: Induced Drag and Conventional Wing Tip Researchmentioning
confidence: 99%
“…The dimension of the tips used in the present study can be compared with different types of models used by other researchers which were inspired by bird wing tips to analyze the aerodynamics of wing tips. Smith et al (2001) have used five winglets each 38.1mm chord and 304.8mm span mounted on a half wing model. Céron-Muñoz et al (2013) have used three sail tips with aspect ratios 2.7, 3.1 and 3.5.…”
Section: Description Of Wingtipsmentioning
confidence: 99%
“…Cosin et al (2010) reported CLmax to be 1.12 at 11ᵒ stall angle for a configuration which has three winglets with cant angles of 30°, 15°, and 0° respectively, that is maximum in six different configurations tested. Smith et al (2001) reported the maximum value between eleven different configurations tested to be 0.8 with different dihedral angles. As per Withers (1981) CLmax for original bird feather tip is 1.2, but in contrast, Tucker (1993) reported CLmax to be more than 2.5 at 15ᵒ angle of attack.…”
Section: Liftmentioning
confidence: 99%
See 1 more Smart Citation
“…Drag reduction by using winglets helps in increasing of payload and increase the range of the aircraft with same fuel consumption. In aircrafts, induce drag is created by the wing tip vortex that is generated due to the difference in pressure between top and bottom surface of the wing near the tip [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%